Hypersurfaces with harmonic curvature in a space of constant Hessian sectional curvature and Betti numbers of Hessian manifolds - Yilmaz, Munevver Yildirim (Academic Journals, 2010)
In this paper, the notion of harmonic curvature for Hessian manifolds of constant Hessian sectional curvature is introduced and two theorems are proved on this subject. Betti numbers of Hessian manifolds that have special features are also studied.
Keywords: Hypersurface; harmonic curvature; Hessian manifold; Betti numbers